Evaluation of Teacher Empowerment Education Program 4th Batch in South Tanggerang Using the Krikpatrick Model - Setiati, Reni; Rugaiyah; Suryadi (International Journal of Applied and Scientific Research, 2024)
The Teacher Empowerment Program (PPGP) is a professional development initiative through education, training, and mentoring that focuses on instructional leadership to promote holistic growth and active, proactive participation of students. The program aims to actively develop educators to implement student-centered learning. This qualitative research employs a narrative approach. The research results show positive behavioral changes in teacher mover after completing PPGP, notably impacting the improvement of classroom learning quality and the cultivation of a learning culture among teachers within the school ecosystem. Although some schools have not fully optimized the growth of a learning culture among their teachers, they are moving in the right direction. Challenges and obstacles are inherent in transformation efforts, reinforcing the appropriateness of the Ministry of Education and Culture's decision to appoint Teacher Empowerment Program participants as school leaders. This move strengthens the force for change and minimizes resistance to or rejection of change.